Vulnerable growth in the euro area: Measuring the financial conditions - Juan Manuel Figueres; Marek Jarocinski (European Central Bank (ECB), 2020)
This paper examines which measures of financial conditions are informative about the tail risks to output growth in the euro area. The Composite Indicator of Systemic Stress (CISS) is more informative than indicators focusing on narrower segments of financial markets or their simple aggregation in the principal component. Conditionally on the CISS one can reproduce for the euro area the stylized facts known from the US, such as the strong negative correlation between conditional mean and conditional variance that generates stable upper quantiles and volatile lower quantiles of output growth.
Keywords: C12; E37; E44; 330; downside risk; macro-financial linkages; quantile regression